Increased non‐relapse mortality due to high‐dose cytarabine plus CY/TBI in BMT/PBSCT for acute lymphoblastic leukaemia in adults. (25th April 2017) - Arai, Yasuyuki; Kondo, Tadakazu; Shigematsu, Akio; Tanaka, Junji; Ohashi, Kazuteru; Fukuda, Takahiro; Kawakita, Toshiro; Mori, Takehiko; Hoshino, Takumi; Onizuka, Makoto; Ozawa, Yukiyasu; Yoshida, Shuro; et al.
Summary: The efficacy of high‐dose cytarabine (HDCA) plus cyclophosphamide/total‐body irradiation (CY/TBI) has been proved in cord blood transplantation (CBT) for acute lymphoblastic leukaemia (ALL), but not in bone marrow or peripheral blood stem cell transplantation (BMT/PBSCT). In this cohort study, we compared the prognosis of CY/TBI ( N = 1244) and HDCA/CY/TBI ( N = 316) regimens in BMT/PBSCT for ALL. The addition of HDCA decreased post‐transplant relapse, while significantly increasing non‐relapse mortality (risk ratio, 1·33), and overall survival was not improved. The positive effects of HDCA reported in CBT cannot be extrapolated to BMT/PBSCT, and HDCA may not be recommended in these procedures.